Australian Dictionary of accounting and finance terms - Robb, Alan J. (Australia : Pitman, 1988)
This dictionary includes several definitions of terms as they are used in Continuously Contemporary Accounting. They are prefixed by '(CoCoA)' in order that the reader may see readily the way in which they differ from the more common definition.
Keywords: Accounting; Dictionary; Finance, terms; English language -- Terms, accounting and finance